1994
DOI: 10.1021/ic00083a001
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray Mass Spectrometry Study of 1:1 Ferric Dihydroxamates

Abstract: In this communication, we report an early example'" of the use of electrospray mass spectrometry (ESMS) to probe the solution structure of transition metal complexes. Iron hydroxamic acid complexes are important due to their relationship to siderophore-mediated iron transport.9 Dihydroxamic acids, such as the siderophore rhodotorulic acid and its synthetic models,lGI4 form 1:l complexes with iron(II1) at low pH. Since this species is an intermediate in the ligand exchange pathway of natural and model ferric di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 2 publications
2
31
0
Order By: Relevance
“…Moreover, the LC–MS analysis of a HA–Fe +3 solution showed additional signals at 455.1 and 491.1 m/z corresponding to a 1 : 1 chloride‐containing complex, [M–H + Fe(III) + Cl 2 + H] + (m/z 491.1) or [M–2H + Fe(III) + Cl + H] + (m/z 455.1). As chloride is a coordinating ligand for iron, it is possible that the chloride anion is directly bound to the metal (Caudle et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the LC–MS analysis of a HA–Fe +3 solution showed additional signals at 455.1 and 491.1 m/z corresponding to a 1 : 1 chloride‐containing complex, [M–H + Fe(III) + Cl 2 + H] + (m/z 491.1) or [M–2H + Fe(III) + Cl + H] + (m/z 455.1). As chloride is a coordinating ligand for iron, it is possible that the chloride anion is directly bound to the metal (Caudle et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Generally, iron-containing signals can be easily identified in the mass spectrum by investigating the isotopic envelope of the signals and detecting the low abundance signal at [MÀ2] þ relating to the stable isotope 54 Fe as described previously. 11,[28][29][30] In addition, the difference of 1 mass unit between the signals of an isotopic envelope revealed that all complexes were singly charged (Fig. 5).…”
Section: Electrospray Ion Trap Mass Spectrometry Of Iron(iii)deferiprmentioning
confidence: 93%
“…Caudle et al 45 used ES-MS to show conclusively that for dihydroxmate ligands with a methylene-bridge linker; the n ϭ 8 species forms monomer whereas the n ϭ 2 species forms a dimer. The naturally occurring nonpeptidic Tris-hydroxamate siderophore, desferrioxamine, possesses a high Fe(III) binding constant and the linker between the two hydroxamates is 9 atoms.…”
Section: The Effects Of Linker Length On Fe(iii) Coordination Modementioning
confidence: 99%
“…Dihydroxamic acids, such as the siderophore rhodotorulic acid and its analogs have been reported to form 1:1 complexes with iron(III) at low pH. [45][46][47] While a cyclic N,NЈ-dihydroxy dipeptide has been reported, 48 to the best of our knowledge, metal-binding properties of N,NЈ-dihydroxypeptides have not been characterized. Compared to hexadentate N,NЈ,NЉ-trihydroxypeptides, tetradentate N,NЈ-dihydroxypeptides possess only two bidentate metal-binding motifs.…”
Section: Introductionmentioning
confidence: 99%